Determining the frequency of Plummer Vinson Syndrome among patients having dysphagia presenting at district Bahawalpur - Nasir Wakeel; Masood Akhtar; Aasma Tariq; Iqra Gull; Hamna Hafeez; Nayab Anjum (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Plummer Vinson syndrome (PVS) is a rare triad of dysphagia, iron deficiency, and esophageal webs. This study aims to assess the frequency of PVS in patients presenting with dysphagia.METHODOLOGY: A cross-sectional study was conducted at the Department of Otolaryngology from 1st April 2020 to 31st March 2021. A total of 164 patients having dysphagia for a minimum of two weeks duration were enrolled. The patient's data was recorded using a pre-designed questionnaire for PVS assessments, complete blood count, serum ferritin levels and barium swallow test results were obtained, and a radiologist was consulted for the upper esophageal web.RESULTS: The observed frequency of PVS among patients with dysphagia was 11(6.7%). Female gender turned out to be significantly associated with PVS occurrence (p=0.001), while age (p=0.748) and duration of dysphagia (p=1.00) showed no significant association with it. Among those with PVS, 72.7% of patients were >40 years of age, 90.9% were females, and 81.8% had a duration of dysphagia >4 weeks. CONCLUSION: It is concluded that PVS is not very frequent among patients with dysphagia. But since it increases the risk of squamous cell carcinoma of the pharynx and the esophagus, therefore, such patients should be followed closely for the presence of PVS and treated promptly to avoid morbidity and mortality.